Three new legskates of the genus Sinobatis (Rajoidei: Anacanthobatidae) from the IndoWest Pacific - Last, Peter R.; Séret, Bernard (Zootaxa, 2008)
Three new species of legskates (Anacanthobatidae) are described from the Indo–Australian region. Two of these species conform to the subgenus Sinobatis Hulley of Anacanthobatis von Bonde & Swart, which is herein elevated to genus level based primarily on clasper morphology. Sinobatis presently includes S. borneensis (South China Sea and Taiwan) and possibly S. melanosoma (East and South China Seas and Taiwan), as well as the new species, S. bulbicauda sp. nov. (eastern Indonesia and northwestern Australia, SE Indian Ocean) and S. filicauda sp. nov. (northeastern Australia, SE Pacific Ocean). The third new species, S. caerulea sp. nov. (northwestern Australia, SE Indian Ocean), is provisionally placed in Sinobatis in the absence of an adult male. The new species are distinguishable from each other, and from nominal Indo–Pacific legskates, based on their morphometrics, meristics, tail morphology and coloration. Legskates exhibit marked intraspecific variation in shape associated with their soft, flexible bodies, and considerable ontogenetic and sexual differentiation.